The Management of Border Protection in the European Union on the Example of the Eastern Border of the Republic of Poland - Piotr Witkowski (Barometr Regionalny, 2019)
The aim of the article is to present the synthetic instruments of managing the external protection of the European Union’s borders and to analyze the level of this protection on the example of identified threats. The current status of this problem is determined by successive immigration crises, modifications of actions taken by organized crime in the field of cross-border illegal/irregular movement of people and goods. The management of the external border protection is particularly important in Polish conditions in which the eastern border is the most important part of the land border of the European Union and the Schengen area. The conducted research allows to verify the research thesis that in relation to the eastern border of the Republic of Poland the actions taken by the European Union institutions, national authorities and uniformed formations contributed to the increase of the level of its protection, which at the same time increases the safety of cross-border movement of people and goods.